AKTINOMISETES KHITINOLITIK DAN PROTEOLITIK SEBAGAI AGEN PENGENDALIAN HAYATI NEMATODA SISTA KUNING (Globodera rostochiensis) - Agustinus Joko Nugroho (Pusbindiklat - LIPI, 2010)
Golden cyst nematode (GCN/Globodera rostochiensis) is a new potato parasitic nematodes found in Indonesia in 2003 and caused great economic losses more than 70% of the production. Due to the problem caused by chemically control (resistancy, killed non target organisms, and environment pollution) development of alternative control measures is a great importance i.g. microbial control. The purpose of this research was to find chitinolytic and proteolytic actinomycetes for controling eggshell nematode which bears vitelin (protein) and chitin. The result found 21 actinomycetes isolates with ratio chitinolytic and proteolytic activities more than 3.0 and among of seven isolates were chitinolytic, 11 isolates were proteolytic and three isolates had double enzyme activities. Seven selected isolates were examined on their chitinase and protease specific activities and ability to degrade nematode eggs. The results showed three isolates had chitinase activity more than 200 IU/mg, four isolates had protease activity more than 300 IU/mg. Results of the bioassay test using crude enzyme on the GCN eggs found that three isolates were able to damage eggs more than 90%. The three isolates can be applied as an agent for biocontrol of GCN in the future.